Push-pull fatigue properties of wires in an iridium: 5% tungsten alloy - Younger, A.; Whitbread, R. C. (College of Aeronautics, 1965)
Introduction. The Materials Department at Cranfield was approached by the Platinum Metals Division of the International Nickel Co. with a view to carrying out a preliminary survey of the fatigue properties of an iridium-5% tungsten alloy. This alloy in drawn wire form is intended for future use in springs subjected to elevated temperatures. For this reason it was decided to investigate both the tensile and the torsional fatigue properties of these wires at room and elevated temperature. This report covers the tensile room temperature properties; subsequent reports will deal with the torsional and the high temperature properties.